(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This topic of the article relates to methodology. The purpose of the article is to study the basic principles of assessment, as well as the importance of a credit-modular system. In this work, a desk study was used to study the principles of assessment, as well as a practical study of the use of authentic materials in the process of teaching English. The key results of this work are the opportunity to comprehend and understand the principles of assessment and further apply them in practice in the field of foreign language teaching.